Asuhan Kebidanan Komprehensif Pada Ny. P Mulai dari Hamil, Bersalin, Nifas, Bayi Baru Lahir dan Keluarga Berencana di Klinik Pratama Riyyan Kaban Jahe Tahun 2021/2022 - Linda Purwanti (Pusat riset dan Inovasi Nasional, 2023)
Pregnancy is a physiological and natural condition that occurs in women. There are various complaints experienced by pregnant women during their pregnancy, one of the most common complaints is dizziness. Objective: LTA provides comprehensive midwifery care to pregnant, maternity, postpartum, BBL, neonate and family planning women using a midwifery management approach for Mrs